Safety and Efficacy of Preoperative Embolization in Patients with Meningioma - Manaka, Hiroshi; Sakata, Katsumi; Tatezuki, Junya; Shinohara, Tadao; Shimohigoshi, Wataru; Yamamoto, Tetsuya (Journal of Neurological Surgery Part B: Skull Base, 2018)
Preoperative embolization for intracranial meningioma has remained controversial for several decades. In this study, we retrospectively reviewed our experience of embolization using particulate embolic material and coil to clarify the therapeutic efficacy, safety, and risk of complication.Methods We reviewed 69 patients who underwent embolization with particulate embolic material followed by surgical resection. An additional 6 procedures were included for patients in whom recurrence was treated, for a total of 75 procedures of preoperative embolization. We analyzed the following clinical data: age, sex, tumor size pathology, complications related to embolization, and surgeon's opinion on the intraoperative ease of debulking and blood transfusion. Embolization was performed mainly from the branches of the external carotid artery.Results No allogenic blood transfusions were needed for any patients. The surgeon had the opinion that whitening and softening of the tumor allowed for easy debulking during decompression of the tumor in most of the patients. Hemorrhagic complications were seen in two patients after embolization. Emergency tumor removal was performed in both of those patients, and they were recovered well after surgery. Transient cranial nerve palsy was seen in one patient. One ischemic complication and one allergic complication occurred.Conclusion Preoperative embolization could give us an advantage in surgery for meningioma. The procedure reduces intraoperative blood loss and operating time by softening the tumor consistency. However, we must pay attention to the possibility of embolic complications and keep the preparation of emergency craniotomy, particularly in patients with large meningiomas.
Keywords: meningioma; preoperative embolization; endovascular technique; surgical treatment